Usia dan Status Perkawinan dengan kejadian Fibroadenoma Mammae di Kota Surakarta - Nur Mahmudah; Povitasari Povitasari; Ayu Indah Sulistyo (Griya Widya: Journal of Sexual and Reproductive Health, 2026)
Background: Breast tumor incidence in Indonesia based on clinical breast examinations shows an increase every year. Fibroadenoma mammae (FAM) is one of the most common types of benign tumors in young women. Several factors that influence the growth of FAM include increased estrogen hormone activity in young women under 30 years of age. Method: The method used in this study was a case-control design, a total of 54 patients were included, divided into 2 groups, 27 FAM patients (cases) and 27 non-FAM patients as controls. The data analyzed by chi square and logistic regression test. Result: The results showed that there was a significant relationship between age and the incidence of FAM (p < 0.05), where patients of reproductive age suffered more from FAM than menopausal patients. A significant relationship between marital status and FAM (p> 0.05), where most FAM suffered from unmarried women. Age and marital status had a 63.1% influence on the incidence of FAM. Implication: The government and public should be aware that fibroadenoma mammary is a risk factor for young and unmarried women, so it is necessary to take preventive measures against the etiology of fibroadenoma mammary which is mainly caused by genetic mutations and marriage reduces the risk of fibroadenoma mammary occurrence. Novelty: This study provides knowledge that age and unmarried status increase the risk of breast fibroadenoma.